Student voice as risky praxis: democratising physical education teacher education. (3rd September 2017) - Enright, Eimear; Coll, Leanne; Ní Chróinín, Deirdre; Fitzpatrick, Mary
ABSTRACT: Background : Student voice agendas have been slow to permeate higher educational institutions. Curricula in universities, like those in primary and secondary education, are still usually made for students by teachers who, while they may have the best interests of the students in mind, rarely if ever engage students in curriculum decision-making. The need for more equitable, dialogic and democratic engagement by students is particularly relevant in the context of teacher education. It has been argued that pre-service teachers should experience democratic practices during their teacher education experiences in order to have the confidence, knowledge and skills to support democratic opportunities in schools. Purpose : Through the participatory action research project described in this paper we sought to position pre-service teachers as pedagogical consultants who would design feedback strategies, gather feedback with faculty and co-construct physical education teacher education (PETE) curricula. We saw this process as a democratic possibility that might create opportunities for pre-service teachers to critique and transform their own educational experiences. In this paper we detail the process we used to support dialogue about teaching and learning between students and faculty members and draw on the perspectives of the students, pedagogical consultant, lecturer and teaching and learning advocate involved in this project. Participants and setting : The project was undertaken with one cohort (77) of pre-service teachers during the final year of a four-year undergraduate PETE programme in an Irish university and focuses on the democratization of one PETE course. Data collection : Data were generated with and by the pre-service teachers, the pedagogical consultant, the lecturer and the regional teaching and learning advocate. The primary data collection methods were interviews and observation. Data analysis : The data were reviewed repeatedly looking for patterns, themes, regularities, paradoxes, variations, nuances in meaning and constraints [Rubin and Rubin 1995. Qualitative Interviewing. The art of Hearing Data . London: Sage]. The authors coded all data sets independently using constant comparison [Glaser 1965. "The Constant Comparative Method of Qualitative Analysis." Social Problems 12 (4): 436–445] and then shared their processes and subsequent codes. Our analysis engages Greene's [1988. The Dialectic of Freedom . New York: Teachers College Press] dialectical theory, to explore how naming and holding the tensions involved in this research and pedagogical enterprise was not stultifying but generative. Findings : Three key dialectics were constructed from the data: student–teacher, critical reflection–learning and responsibility–accountability. We speak to each of these themes from the perspectives of the students, the pedagogical consultant and the lecturer who participated in this project. Discussion and conclusion : Our discussion turns to the challenges and benefits associated with the pursuit and realization of democratic possibilities in PETE.